Resistance to the legume pod borer, Maruca vitrata Fabricius and the probable modalities involve in wild Vigna - Jackai, L.E.N.; Padulosi, S.; Ng, Q. (Elsevier, 1996)
A large number of accessions belonging to selected wild Vigna species namely V. unguiculata subspecies dekindtiana, V. oblongifolia, and V. vexillata were evaluated using choice (DCAT) and no-choice (NCFT) laboratory feeding bioassays to determine their resistance to the pod borer, Maruca vitrata Fabricius. The most resistant accessions belonged to V. vexillata, followed by those from V. oblongifolia, with a few outstanding exceptions from V. unguiculata. Even though the latter were the least resistant, they provided the greatest variability among the tested accessions. In the DCAT, the cultivated cowpea line, IT84S-2246, which was used as the susceptible control was always preferred for feeding by the larvae (feeding index [FI] of 1.10–2.60) than the V. unguiculata accessions (FI ranged from 0–0.52). Against the resistant control (itself belonging to V. vexillata), only a few accessions were less preferred, most of these being either V. vexillata or V. oblongifolia. Larvae lost weight on the most resistant from all three species, because they either did not feed, or fed very little. Weight gain was positively correlated with seed damage (r = 0.82, P < 0.01) and the amount of frass produced (r = 0.91, P < 0.01). Seed damage was also positively correlated with the amount of frass produced (r = 0.64, P < 0.05). On the basis of these results, we believe that both antibiosis (post-ingestive effects) and antixenosis (deterrence to boring into the pods to feed) modalities of resistance are involved. The results are discussed further in relation to the origin, domestication and use of these accessions in cowpea improvement.